PELAKSANAAN PEMBELAJARAN KETERAMPILAN PENGGUNAAN TONGKAT BAGI ANAK TUNANETRA - Theresia Sijabat Mona (Universitas Negeri Padang, 2012)
This research is plane from the term inclusi trend right now. Till low, the average of the child is 50-60. So this research is process for blind child, the constraints must be up against in education process and efforts to surpass the constraint in orientasi and mobilitas education process. This research use qualitative approach with qualitative descriptive research type. Subyect of the research is a teacher class, data source support is special cainselor teacher and the headmaster in SLB-A Payakumbuh. Collecting data process are pass trought by observation, interview, and documentation.The yield process indicate in education process, teacher not adjust RPP with the characteristic of the blind child. In the realization once in a while use exact media till in Orientasi andmobilitas education process. The child feel difficult to understand the matter. The constraint become because the teacher not yet understand characteristic of the blind child, till result the child always get low value in mathematic lesson. The effort in experience constraint is with always prepare real media of concrete, concord with lesson matter. The teacher must always prepare concrete media and realize modification to make RPP is concord with characteristic of the blind child.